E-Catalogue of Wayang Kulit Purwa Collection at Museum Wayang Kekayon Yogyakarta - Dewi Nofitasari; Trisna Pradita Putra; Dian Ajeng Kirana (Institut Seni Indonesia Yogyakarta, 2024)
Museum Wayang Kekayon Yogyakarta is one of the museums in Indonesia that boasts a wide variety of wayang (shadow puppetry) collections. Founded by Prof. Dr. dr. KPH. Soejono Prawirohadikusumo, Sp. S, Sp.Kj. (K), better known as the late Pak Soejono, this museum serves as a cultural heritage site from the past, emphasizing the importance of preserving and maintaining its collections due to their significant cultural value. Various methods are employed to ensure these collections are preserved while also serving as educational tools for future generations. One such method is the creation of the museum's E-Catalog. The primary goal of the E-Catalog collection is to identify the museum's collections. The creation of the E-Catalog Collection of Museum Wayang Kekayon specifically focuses on the type of leather puppet (wayang kulit purwa) collections. All data is gathered through observation, interviews, and documentation. The process of creating the collection catalog involves several steps, including preparation (related to permissions and artwork reviews), Action Work (taking photos, recording, measuring, and checking each collection), Intellectual Work (writing museum biographies and wayang descriptions), Compilation of materials and information, creation of collection catalog layout designs, and presenting the catalog collection results on the website in flipbook format. The collection catalog contains general information and descriptions of 75 wayang kulit purwa collections. These collections are classified based on wayang characters such as gunungan (mountain-shaped screen), gods, Ramayana characters, and Mahabharata characters. With the creation of this collection catalog, it serves as education for the public regarding archives and wayang, enriching cultural knowledge and appreciation.